Frequency Estimation in DSOGI cells by means of the Teager Energy Operator - Pigazo, Alberto; Azcondo, Francisco J.; Branas, Christian; Lamo-Anuarbe, Paula (Proceedings of the IEEE Workshop on Computers in Power Electronics, COMPEL, 2023)
Second Order Generalized Integrator (SOGI) cells are used for notch filtering due to their simplicity and harmonic rejection capability. SOGI and Dual SOGI (DSOGI) filter cells, combined with Frequency Locked Loops (FLL) to adjust the notch frequency, are commonly used in both single-and three-phase grid following (GFL) power converters for synchronization, i.e. SOGI-FLL and DSOGI-FLL, respectively. The FLL relies on a gradient descent method to minimize a cost function built up around one inner SOGI cell variable, the in-quadrature voltage estimation, and one outer variable, the error signal due to the SOGI filter cell. As a result, the FLL generates relatively large DC offsets and harmonic distortion passing through the outer SOGI cell variable, which deteriorates the frequency estimation and then, the SOGI-FLL performance. To attenuate these issues, the method proposed only uses inner SOGI cell variables. It minimizes the deviation between the estimated grid frequency and the frequency of the signal across the SOGI cell, which is detected through the Teager Energy Operator (TEO). The proposal is validated in simulation and experimentally.
Keywords: converter; PLL; second order generalized integrator; synchronization; three-phase; Scopus(2); WOS(2)